Menjalin Relasi Tuhan, Manusia dan Alam Melalui Tradisi Mane’e - Silvianus Fidelis Bentalen; Marco Y. Mamarodia; Giovani Diamanti (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2026)
The modern ecological crisis, characterized by the excessive exploitation of marine resources demands solutions that go beyond formal policies and technological innovations. This research explores the Mane’e tradition on Kakorotan Island, Talaud Islands, as a model of local wisdom that integrates spiritual, social, and ecological dimensions in environmental preservation. Utilizing a descriptive qualitative method with a literature review approach, this study analyzes how Mane’e represents the harmonious relationship between God, humanity, and nature. The results indicate that the Mane’e tradition—through the customary prohibition system (Eha) and environmentally friendly fishing techniques (Sam’mi)—has proven effective in maintaining the sustainability of marine ecosystems. Socially, Mane’e strengthens community cohesion through the spirit of mutual cooperation (gotong royong) and a fair distribution system (Matahia Ina). Spiritually, the ritual affirms the position of nature as a trust from the Creator that must be held sacred. This research concludes that Mane’e is not merely a fishing technique, but a philosophy of life and a form of spiritual-ecological literacy relevant as an alternative solution for environmental conservation in the modern era. Efforts in youth education and legal protection are essential to ensure these noble values endure amidst the currents of modernization.